Factors that Influence the Firm Value in Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange 2013 – 2017 - Amilus Sholikhah (The Indonesian Accounting Review, 2018)
Firm value is the price of company’s stock in the capital market that must be paid by an investor if he wants to own the company. Every company aims to maximize the fi rm value because with a high fi rm value, investors assume that the company’s performance is better and has prospects in the future so that investors will be interested to invest in the company. Optimizing the fi rm value can be done with the implementation of fi nancial management functions. Financial management involves decisions made by the company. This research aims to fi nd out the infl uence of dividend policy, debt policy, investment decision, and profi tability on the fi rm value. The population in this study is consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) period 2013-2017. A sample of 12 companies is obtained by using purposive sampling method. Analysis techniques used are statistical analysis and multiple linear regression analysis with SPSS 16. The results of this study show that the variables of dividend policy, debt policy, investment decision, and profi tability have an effect on the fi rm value.